Enhancing heat transfer in a heat exchanger: CFD study of twisted tube and nanofluid (Al2O3, Cu, CuO, and TiO2) effects - Ghazanfari, Valiyollah; Taheri, Armin; Amini, Younes; Mansourzade, Fatemeh (Case studies in thermal engineering, 2024)
This study investigates the influence of nanofluids on heat exchanger efficiency using 3-D computational fluid dynamics (CFD). The objective is to optimize the performance of twisted tubes by analyzing various pitch lengths (P = 180, 135, 90, 67.5, and 45 mm). The method's accuracy is validated by comparing experimental and numerical data from previous studies. The analysis focuses on key parameters such as heat transfer factors, outlet temperatures, and pressure drops, encompassing a wide range of flow rates (0.5 kg/s to 2 kg/s). The findings demonstrate that using nanofluids in twisted tubes significantly enhances heat transfer while slightly increasing pressure drop. Specifically, when compared to the smooth tube device with six baffles, employing 0.1 vol% Cu and 0.15 vol% Al2O3 nanoparticles in the twisted tube with a pitch length of 45 mm leads to heat transfer improvements of 1.04 and 1.12 times, respectively. Moreover, eliminating baffles favoring the optimized twisted tube configuration results in a notable reduction in pressure drop by approximately 1.55 times. These results highlight the potential of nanofluid implementation in enhancing heat exchanger efficiency and offer valuable insights for designing and optimizing heat transfer systems in various industrial applications.